FOR THE FIFTIETH ANNIVERSARY OF THE UNIVERSITY BULLETIN «PHILOSOPHICAL PERIPETIAS» - «Філософських перипетій», Редакція (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
Тhe first issue of the university bulletin from the series "Philosophy" was published in 1965. Issues of this trend have created one of the most powerful creative "platforms" for the publication of the results of philosophical research of scientists of Kharkov, and also joined to support and expand the nationwide (and even international) philosophical dialogue.